2016
DOI: 10.1016/j.jacc.2016.07.739
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Development of a MicroRNA-Based Therapy for Elderly Patients With Myocardial Infarction

Abstract: We concluded that miR-22 is an important regulator of cardiac autophagy and a potential therapeutic target, especially in the older myocardium. Finally, circulating miR-22 provides prognostic information for HF patients, highlighting miR-22 as a promising therapeutic and biomarker candidate for cardiovascular disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 27 publications
5
69
0
Order By: Relevance
“…The increase in cardiac miR-22 levels during aging was paralleled by a progressive decline in myocardial autophagy. Importantly, miR-22 inhibition appears to rescue autophagy in aging hearts (11). miR-22 may have autophagy-independent actions, and thus, the causative involvement of autophagy in mediating the salutary actions of miR-22 inhibition remains to be demonstrated.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…The increase in cardiac miR-22 levels during aging was paralleled by a progressive decline in myocardial autophagy. Importantly, miR-22 inhibition appears to rescue autophagy in aging hearts (11). miR-22 may have autophagy-independent actions, and thus, the causative involvement of autophagy in mediating the salutary actions of miR-22 inhibition remains to be demonstrated.…”
mentioning
confidence: 97%
“…Using high-throughput screening based on the fluorescence-activated cell sorting-based detection of GFP-LC3 protein and library screening, Gupta et al identified miR-22 as a strong inhibitor of autophagy in cardiomyocytes (11). The authors showed that miR-22 inhibits the reduction in GFP-LC3 signal in response to starvation, an established stimulus for autophagy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gupta et al employed an aged mice model to study the effect of anti-miR22 therapy following AMI and, compared to younger mice, old mice were shown to have higher expression levels of miR-22, a key regulator for cardiac autophagy [65]. for the cardiac hypertrophy in HF murine models [69].…”
Section: Mir-based Therapy For Cardiovascular Diseasesmentioning
confidence: 99%
“…A 4-miRNA panel including miR-150 improved outcome prediction in a cohort of 150 AMI patients (9). In a recent case/control study with 198 patients, circulating levels of miR-22 were independent predictors of cardiovascular mortality in patients with systolic heart failure from both ischemic and nonischemic origin (10).…”
mentioning
confidence: 99%